Saúde em tempos ultraneoliberais: entre a atenção psicossocial e a (re)manicomialização - Hoffmann, Edla; Pereira Freitas, Lyzete Bruna (Argumentum, 2023)
This article analyses the permanent fiscal adjustment regarding mental health policy that have resurged under ultra-neoliberalism, the return of asylum practices, and the commodification of life in Brazil. Documentary analysis was conducted to understand public budget allocations for mental health policies using secondary data available on the Brazilian federal government websites and institutional documents. Results show the potentiation of the contradictions of the Brazilian Unified Health System and Psychosocial Care Network, intensified by fiscal austerity policies and public spending below user needs and to the detriment of capital. Its effects are harmful when confronted by the Covid-19 pandemic and setbacks regarding psychosocial care, pointing to a significant return of (re)asylum care with an emphasis on Therapeutic Communities.